Analisa Waktu Bongkar Muat Kapal Peti Kemas Pada Terminal III Pelabuhan Tanjung Priok Jakarta - Kurniawan, M.; Putra, Riki Wanda; yohandrey, fitra_ (Jurnal Cakrawala Bahari, 2025)
Port of Tanjung Priok, Indonesia, faces excessive ship and container dwell times—particularly at Terminal III—driven by container traffic growth that outstrips the capacity of handling facilities. This study analyzes container ship handling time (dwell time), assesses the impact of adding ship-to-shore cranes, and estimates the required berth length and yard area based on projected container flows. Secondary data on container throughput for 2009–2013 were used and projected forward to 2014–2018. Queueing analysis was performed with an M/M/c model to obtain standard system performance metrics (L, Lq, W, Wq), which were then converted into dwell-time estimates; berth and yard requirements were calculated using berth-throughput approaches and standard space requirements per TEU. Results indicate that under the existing equipment level of 39 cranes, dwell time rose from about 6.92 days in 2009 to more than 14 days in 2012–2013, substantially exceeding operational standards. Simulations show that increasing the number of cranes to 51–55 units would reduce dwell time to approximately 5.85–6.82 days. Projected infrastructure needs for 2018 include an aggregate berth length of roughly 7,339 m and a stacking yard area of about 168.9 hectares. The findings underscore the urgent need for additional handling equipment and infrastructure development and point to opportunities for enhancing analysis and operational monitoring through the application of artificial intelligence for dwell-time prediction and real-time smart-port management.